Homoeopathic Management of Polycystic Ovarian Syndrome (Homoeopathy for All, 2025)
Polycystic ovarian syndrome (PCOS) was originally described in 1935 by Stein and Leventhal. as a syndrome manifested by amenorrhea, hirsutism and obesity associated with enlarged polycystic ovaries. PCOS is a syndrome of ovarian dysfunction along with the cardinal features of hyperandrogenism and polycystic ovary morphology. Its clinical manifestations include menstrual irregularities, signs of androgen excess (e.g. hirsutism) and obesity. It can be very wonderfully management by homoeopathy with the great effects of homoeopathic medicine & our holistic approach.
Keywords: PCOS; Menstrual complaint; obesity; female menstrual complaint; amenorrhea